Pre-emergence herbicides effects in no-till soybean system with Panicum maximum ‘BRS Tamani’ - da Silva, Mateus Matos; Almeida, Edmilson Igor Bernardo; de Sousa, Andreza Maciel; Ponte, Islana Silva; Ribeiro, Bruna da Silva Brito; de Sousa, Daniel Lobo; de Sousa, Andressa Carvalho; da Silva Sousa, Washington; de Oliveira, Leonardo Bernardes Taverny; Souza, Jarlyson Brunno Costa [UNESP] (Southern Cross Publishing, 2024)
The use of pre-emergence herbicides is an important strategy in resistant-weeds management, but its performance can be affected in no-till systems. This study aimed to analyse weed control from pre-emergence herbicides in no-till soybean system with Panicum maximum cv. BRS Tamani. The experiment was conducted in randomized block design with eight treatments and five repetitions. The treatments consisted in no-treatment, S-metolachlor + imazethapyr (1,200.00 g a.i. ha−1 + 100.00 g a.e. ha−1, respectively), S-metolachlor + fomesafen (1,035.66 g a.i. ha−1 + 227.70 g a.e. ha−1, respectively), S-metolachlor + diclosulam (1.200.00 g a.i. ha−1 + 29.40 g a.i. ha−1), imazethapyr + diclosulam (100.00 g a.e. ha−1 + 29.40 g a.i. ha−1), imazethapyr + flumioxazin (100.00 g a.e. ha−1 + 50.00 g a.i. ha−1), pyroxasulfone + flumioxazin (90.00 g a.i. ha−1 + 60.00 g a.i. ha−1) and pendimethalin (1,137.50 g a.i. ha−1). We evaluated weed phytosociological rates, weed control, and soybean growth. We identified 23 weed species distributed in 22 genera and 15 botanical families, majority of eudicotyledonous botanical class (78.2%), annual life cycle (56.5%), and sexual reproduction (100%). The integrated weed management, between herbicides and straw, was effective in herbicide-resistant weed control, except Euphorbia heterophylla. The treatments recommended included S-metolachlor combinations with fomesafen, imazethapyr, diclosulam, and also, pyroxasulfone + flumioxazin. The Panicum maximum cv. BRS Tamani straw was estimated in 11 t ha−1 and influenced negatively herbicides lipophilics and with slower movement, such as pendmethalin.